Differential effects of copper sulfate (CuSO4) and copper tetraamine sulfate complex ([Cu(NH3)4]SO4) on Cu-enzyme activities, Cu and Fe levels, and lignin deposition in Cu-deficient tobacco (Nicotiana rustica) plants - Bahrami-Rad, Sara; Hajiboland, Roghieh (Acta physiologiae plantarum, 2024)
Knowledge of the effect of different copper (Cu) chemical forms and their application mode on meeting the plant’s Cu requirement is much more limited than that of other micronutrients. In this work, hydroponically-grown tobacco ( Nicotiana rustica L . ) plants were pre-cultured for thirty days under Cu-sufficient and Cu-deficient conditions, then the Cu-deficient plants were resupplied with 0.5 µM CuSO 4 (CuSu) or Cu tetraamine sulfate complex ([Cu(NH 3 ) 4 ]SO 4 ) (CuAm) through roots or leaves. The biomass of plants was resumed almost equally by both chemical forms of Cu. Cu’s leaf and root concentrations exhibited a more pronounced response to CuSu application. In contrast, the restoration of the activities of Cu-containing enzymes (superoxide dismutase, polyphenol oxidase, diamine oxidase) was either similar to or, in some cases, even higher when CuAm was applied. The leaf iron concentration was also diminished under Cu starvation and increased by Cu resupply more effectively by CuAm. The activity of phenylalanine ammonia-lyase and peroxidase, phenolics accumulation, and lignin deposition was significantly influenced by Cu deficiency and resupply. Foliar-applied CuAm and root-applied CuSu were the most effective treatments for the resumption of lignin concentration. Results showed efficient re-translocation of foliar-applied Cu. However, the activity of defense enzymes and lignin content suggests that foliar spraying likely induced mechanical stress in the leaves. Furthermore, the effect of the accompanying ion (NH 4 + ) was likely the mechanism for the superior effect of CuAm in the induction of structural strength through lignin deposition and improvement of Fe uptake in plants compared with CuSu.